2001
DOI: 10.1093/emboj/20.24.6997
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell movement and assembly of a plant closterovirus: roles for the capsid proteins and Hsp70 homolog

Abstract: Diverse animal and plant viruses are able to translocate their virions between neighboring cells via intercellular connections. In this work, we analyze the virion assembly and cell-to-cell movement of a plant closterovirus and reveal a strong correlation between these two processes. The ®lamentous virions of a closterovirus possess a long body formed by the major capsid protein (CP) and a short tail formed by the minor capsid protein (CPm). Genetic and biochemical analyses show that the functions of these vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 66 publications
1
130
0
3
Order By: Relevance
“…It was demonstrated that, in the absence of functional CPm, CP is capable of encapsidating the entire BYV genome (23), suggesting that the tail has not evolved merely for RNA protection. Because the Hsp70h, p64, and CPm are each required for BYV cell-to-cell movement, it was proposed that the tail represents a viral transport device (17,23). This interpretation seems to be even more likely in relation to the tip segment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that, in the absence of functional CPm, CP is capable of encapsidating the entire BYV genome (23), suggesting that the tail has not evolved merely for RNA protection. Because the Hsp70h, p64, and CPm are each required for BYV cell-to-cell movement, it was proposed that the tail represents a viral transport device (17,23). This interpretation seems to be even more likely in relation to the tip segment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that the BYV Hsp70h and p64 proteins are required for assembly of the virion tails, but not the bodies (17,23), suggesting that each of these proteins is an integral tail component. It was also suggested that the tails are assembled in the proximity of the RNA 5Ј terminus, although the length of the RNA fragment encapsidated by the tails was not determined (29).…”
Section: Molecular Composition Of Virion Tailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these proteins, Hsp70h may be the key element of BYV transport machinery, since this protein, when expressed in the absence of other viral products, is able to localize to motile granules, which are transported to the cell periphery in an actin-dependent manner, and can associate with plasmodesmata (Prokhnevsky et al, 2005). Moreover, the ATPase activity of Hsp70h is required for cell-to-cell BYV transport (Alzhanova et al, 2001).…”
Section: Role Of Virions In Cell-to-cell Transport Of Filamentous Virmentioning
confidence: 99%
“…Hsp70h is a multi-functional protein which possesses several conserved motifs such as those involved in ATPase activity [39]. The crinivirus-encoded Hsp70h may be associated with virion tail assembly and disassembly similar to the closterovirus Beet yellows virus (BYV) [9]. Further, Hsp70h may be involved in plasmodesmatal attachment and virion translocation through ATPase activity [9].…”
Section: Molecular Biologymentioning
confidence: 99%